Key Performance Indicators for an Information System in Indian Banking Sector: An Empirical Investigation - Sharma, Neeraj; Sehgal, R.K.; Goyal, D.P. (Gyan Management Journal, 2009)
The objective. of this study is to identify the Key Performance Indicators (KPls} of Information system in Indian Banking Sector. An empirical investigation into the malter is necessary. Measuring and evaluating performance is a critical factor for ensuring the success of IS in a bank. IS should be evaluated from the perspective of Strategic Integration, Functional Integration, and Technological Integration. In the current study, the identification of key performam:e indicators has been restricted to the post implementation process. Though the proposed evaluation process is generic in nature, it has been developed and tested by keeping the scope of tudy as the Banking industry in the tricity region of Chandigarh, Mohali, and Panchkula of India. This industry has been chosen as it has been one of the early adopters of the technology. ft is found in the study that there are 12 factors or Key Performance Indicators that are important for evaluating the Information System in the bank.
Keywords: KPI of IT; Indian Banking Sector; Factor Analysis